The Cost Claims due to Extension of Time on Construction Contracts (Case Study: Power Plant Project) - Roni Febrianto; Sami'an; Sarwono Hardjomuljadi (International Journal of Law Policy and Governance, 2025)
Delays in the execution of construction contracts are common occurrences and are generally understood to be the contractor's responsibility. In practice, however, delays in construction contracts can also be caused by factors beyond the contractor's control or responsibility, leading to an extended duration for project completion. Delays that are not attributable to the contractor grant the contractor the right to a time extension. Such extensions of time often trigger cost claims resulting from delays in work execution that are not the contractor's fault, as the contractor incurs additional costs due to the extended of project completion. This paper discusses the primary causes extension of time and the mechanisms for resolving cost claims arising from these extensions based on legal principles, including pacta sunt servanda, the principle of fairness, and the risk theory in contracts. The research employs a qualitative approach involving contract document analysis, case studies, and literature reviews. The findings indicate that excusable and compensable delays provide a legitimate basis for contractors to propose cost claims, while non-excusable delays may result in penalties for the contractor. This paper offers practical and theoretical recommendations for more effectively managing cost claims due to extension of time and highlights the importance of risk allocation in construction contracts.